2023
DOI: 10.1177/01492063221143714
|View full text |Cite
|
Sign up to set email alerts
|

Disability Severity, Professional Isolation Perceptions, and Career Outcomes: When Does Leader–Member Exchange Quality Matter?

Abstract: Employees with disability-related communication impairment often experience isolation from professional connections that can negatively affect their careers. Management research suggests that having lower quality leader relationships can be an obstacle to the development of professional connections for employees with disabilities. However, in this paper we suggest that lower quality leader–member exchange (LMX) relationships may not be a uniform hurdle for the professional isolation of employees with disabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…The higher quality level of LMX not only provides higher support of leaders to their subordinates but also gives empowerment and motivation (Young et al, 2021), for the smooth accomplishment of organizational goals. Also, this higher relationship (e.g., LMX) increases the workplace and career outcomes of the employees (Lyons et al, 2023). Employees benefit most from their supervisor's encouragement and adaptability when they can engage with them in a relatively casual environment (Adhyke et al, 2023).…”
Section: Leader-member Exchange As Mediatormentioning
confidence: 99%
See 1 more Smart Citation
“…The higher quality level of LMX not only provides higher support of leaders to their subordinates but also gives empowerment and motivation (Young et al, 2021), for the smooth accomplishment of organizational goals. Also, this higher relationship (e.g., LMX) increases the workplace and career outcomes of the employees (Lyons et al, 2023). Employees benefit most from their supervisor's encouragement and adaptability when they can engage with them in a relatively casual environment (Adhyke et al, 2023).…”
Section: Leader-member Exchange As Mediatormentioning
confidence: 99%
“…Employees benefit most from their supervisor's encouragement and adaptability when they can engage with them in a relatively casual environment (Adhyke et al, 2023). It has also been observed that a higher level of LMX reduces the negative emotions, attitudes, and behaviors of the subordinates and enables them to deal with interpersonal workplace challenges positively (Lyons et al, 2023). When leaders focus on the development of their team members, they can create a sense of shared vision and purpose, which can help to create a strong sense of camaraderie among team members, and TFTL often uses this sense of harmony to build relationships with team members (Ha, 2022;Sun et al, 2022).…”
Section: Leader-member Exchange As Mediatormentioning
confidence: 99%